OPTIMALISASI PEMERATAAN PENDIDIKAN NON-FORMAL DAN KEWIRAUSAHAAN PADA ANAK PMI DI MALAYSIA MELALUI PENDEKATAN MULTIDISIPLIN - Verdiana, Maishifa Avis; Janah, Dyah Laily Miftakul; Veronicha, Silvia; Hositanisita , Hastrin; Wibowo , Febrian Wahyu (Jurnal Abdi Insani, 2025)
International Thematic Real Work Lecture (KKN-T) activities in Malaysia aim to optimize sharia financial literacy, entrepreneurial skills, character education and healthy lifestyles in Indonesian children. The implementation process involved selecting research subjects from children registered at Sanggar Guidance SIKL (Sekolah Indonesia Kuala Lumpur). Observation and qualitative analysis methods are used to evaluate community involvement and the impact of the programs implemented. The main results show an increase in children's understanding of Islamic finance concepts and entrepreneurial skills, with statistically significant effect sizes in the subject groups involved. These findings underline that a multidisciplinary approach in community activities can have a substantial positive impact on developing children's competencies, as well as building awareness of the importance of sharia financial literacy, entrepreneurial skills, character education and healthy lifestyles. The conclusion of this research emphasizes that active community involvement, supported by the collaboration of various parties, is able to create sustainable results for the development of Indonesian children in Malaysia, as well as instill character values ​​that are essential for their future.